АСТРОНОМИЯ КУРСИНИ ЎҚИТИШ ЖАРАЁНИДА ПЕДАГОГИК ТЕХНОЛОГИЯЛАРНИНГ ЎРНИ ВА АҲАМИЯТИ - Ешбаева, М. (SCIENCE and SOCIETY, 2020)
The article discusses the issues of increasing the creative and cognitive activity of students using pedagogical technologies in practical lessons to strengthen theoretical knowledge in teaching astronomy. Such technologies are easily absorbed by students, as they involve the use of student experience, have the potential for active creative research and thinking experiments.